Bottle top fish scaler - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
A simple and effective fishscaler has been developed by the FAO/DANIDA Training Project On Fish Technology. Serrated bottle caps (i.e. beer or mineral water type) are loosely nailed to allow rotation on a piece of wood shaped like a square bat. The...